Antibiotic resistance of microbial community of the lake Baikal ecosystem in the area of Listvyanka, Slyudyanka and Baikalsk - E. V. Verkhozina; V. A. Verkhozina; E. D. Savilov; V. V. Verkhoturov (Acta Biomedica Scientifica, 2014)
The article presents the results of study of antibiotic resistance of bacteria isolated from the lake Baikal ecosystem. It was revealed that in the littoral zone of the lake Baikal (area of Listvyanka, Baikalsk, Slyudyanka) under the anthropogenic impact there are strains of microorganisms resistant to a wide range of antibiotics. Strains resistant to all antibiotics are 1 % of the isolated bacterial strains; strains sensitive to all antibiotics are 6 %; strains isolated from the drill samples of bottom sediments are 80 %. This phenomenon can be considered as an indicator of anthropogenic influence.